Perbandingan belanja negara dimasa sahabatan umar bin khattab dan pemerintah indonesia saat ini - SYARIF, MUH HAIQAL (Maliki Interdisciplinary Journal, 2025)
This article examines a comparison between the state expenditure system during the leadership of Caliph Umar bin Khattab and the state budget system in modern-day Indonesia. The study is motivated by the need to understand how the concept of a just and people-oriented public finance system was implemented in early Islamic governance, and how these principles remain relevant to today’s budget management. During Umar bin Khattab’s rule, state spending focused on fulfilling basic societal needs, providing social security, and supporting simple yet functional public infrastructure. The financial system was managed directly, transparently, and with great accountability under exemplary leadership. In contrast, Indonesia’s current state expenditure is implemented through a modern budgeting system governed by the State Budget Law (APBN), with various allocations for sectors such as education, healthcare, infrastructure, and debt financing. Despite its more advanced administrative structure and financial technology, Indonesia still faces major challenges including corruption, bureaucratic inefficiencies, and a lack of effectiveness in budget distribution. This article adopts a descriptive comparative approach to highlight the fundamental differences in fiscal management principles between the two periods and draws essential lessons from Umar bin Khattab’s leadership as a source of inspiration for improving contemporary budget governance. It is hoped that these historical insights can help guide efforts to strengthen fiscal accountability and justice for the public good.